Strategi Pola Komunikasi Keluarga Katolik di Era Digital - Tampubolon, Benny Ariandi (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to examine Catholic families' strategies in building effective communication patterns and educating their children with moral, intellectual, and religious values in the digital era.Method – The method used is qualitative research with observation, interviews, and documentation conducted at Stasi Santo Matias Rasul Simpang Empat Paroki Santo Pius X Aek Kanopan. Primary data was obtained from interviews and direct observation of the family, while secondary data was obtained from relevant literature.Findings – The research findings show that Catholic parents play an important role as faith educators by encouraging participation in mass celebrations and religious activities, and teaching the importance of prayer both individually and corporately. In addition, parents as providers of love teach good manners, respect for others, and responsibility through modeling good actions. Parents also serve as role models in communication by teaching good and polite ways to communicate, and building openness in communication to create a good relationship between parents and children. Research Implications – The implication of these findings is that the strategies implemented by Catholic parents can shape children's characters into independent and qualified individuals in the future. By implementing these strategies, Catholic families can create harmonious communication and support the moral, intellectual, and spiritual development of their children in facing the challenges of the digital era.